Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $h \in \mathcal{C}:=C([-a,a])$, where $a>0$. Prove that there exists a unique function $f \in \mathcal{C}$ such that $$ f(x)=\frac{x}{2}f\Big(\frac{x}{2}\Big)+h(x)\quad \forall x \in [-a,a]. $$

share|improve this question

2 Answers 2

up vote 4 down vote accepted

Uniqueness Let $f_1, f_2 \in \mathcal{C}$ be solutions of $$ f(x)=\frac{x}{2}f\big(\frac{x}{2}\Big)+h(x) \quad \forall x \in [-a,a]. $$ Then for every $x \in [-a,a]$ we have $$ |f_1(x)-f_2(x)|=\frac{|x|}{2}\Big|f_1\big(\frac{x}{2}\Big)-f_2\big(\frac{x}{2}\Big)\Big|. $$ Therefore, for every $x \in [-a,a]$ and every $n \in \mathbb{N}$ we have $$ |f_1(x)-f_2(x)|=\frac{|x|^n}{2^{1+2\ldots+n}}\Big|f_1\big(\frac{x}{2^n}\Big)-f_2\big(\frac{x}{2^n}\Big)\Big|=\frac{|x|^n}{2^{n(n+1)/2}}\Big|f_1\big(\frac{x}{2^n}\Big)-f_2\big(\frac{x}{2^n}\Big)\Big|. $$ Hence $$ \|f_1-f_2\|\le\frac{a^n}{2^{n(n+1)/2}}\|f_1-f_2\| \quad \forall n \in \mathbb{N}. $$ Since $$ \lim_{n\to \infty}\frac{a^n}{2^{n(n+1)/2}}=0, $$ it follows that $f_1\equiv f_2$.

Existence Let $g \in \mathcal{C}$ be arbitrary. Consider the sequence $(f_n)_n\subset \mathcal{C}$ given by $$ f_1(x)=g(x),\ f_n(x)=\frac{x}{2}f_{n-1}\Big(\frac{x}{2}\Big)+h(x) \quad \forall x \in [-a,a] $$ For every $n$ and every $x \in [-a,a]$ we have \begin{eqnarray} |f_n(x)-f_{n+1}(x)|&=&\frac{|x|}{2}\Big|f_{n-1}\Big(\frac{x}{2}\Big)-f_n\Big(\frac{x}{2}\Big)\Big|\\ &\vdots&\\ &=&\frac{|x|^{n-1}}{2^{1+2\ldots+(n-1)}}\Big|f_1\Big(\frac{x}{2^{n-1}}\Big)-f_2\Big(\frac{x}{2^{n-1}}\Big)\Big|\\ &\le&\frac{a^{n-1}}{2^{n(n-1)/2}}\|f_1-f_2\|, \end{eqnarray} i.e. $$ \|f_n-f_{n+1}\|\le \frac{a^{n-1}}{2^{n(n-1)/2}}\|f_1-f_2\| \quad \forall n \ge 1. $$ Hence, for every $m>n \ge 1$ we have \begin{eqnarray} \|f_n-f_m\|&\le&\sum_{k=n}^{m-1}\|f_k-f_{k+1}\|\le \|f_1-f_2\|\sum_{k=n}^{m-1}\frac{a^{k-1}}{2^{k(k-1)/2}}\le \|f_1-f_2\|\sum_{k=n}^\infty\frac{a^{k-1}}{2^{k(k-1)/2}} \end{eqnarray} From the latter inequality we obtain that $$ \lim_{m,n\to \infty}\|f_n-f_m\|=0, $$ i.e. $(f_n)$ is a Cauchy sequence, it therefore converges to some $f \in \mathcal{C}$. From the definition of $f_n$ we get for each $x \in [-a,a]$: $$ f(x)=\lim_nf_n(x)=\lim_n\Big(\frac{x}{2}f_{n-1}\Big(\frac{x}{2}\Big)+h(x)\Big)=\frac{x}{2}f\Big(\frac{x}{2}\Big)+h(x). $$

share|improve this answer

If $f$ is a solution then for all $x \in [-a,a]$ we get by applying the functional equation $n$ times \begin{align*} f(x) &= \frac{x}{2} f\left(\frac{x}{2}\right) + h(x)\\ &= \frac{x^2}{2^{1+2}} f\left(\frac{x}{4}\right) + \frac{x}{2} h\left(\frac{x}{2}\right) \\ &= \frac{x^2}{2^{1+2+3}} f\left(\frac{x}{8}\right) + \frac{x^2}{2^{1+2}} h\left(\frac{x}{4}\right) + \frac{x}{2} h\left(\frac{x}{2}\right) + h(x)\\ &= \ldots\\ &= \frac{x^n}{2^{n(n-1)/2}} f\left(\frac{x}{2^n}\right) + \sum_{k=0}^{n-1} \frac{x^k}{2^{k(k-1)/2}} h\left(\frac{x}{2^k}\right) \end{align*} The first summand tends to zero for $n \to \infty$, as do the summands inside the second sum for $k \to \infty$. So we would like to define $$f(x) = \sum_{k=0}^{\infty} \frac{x^k}{2^{k(k-1)/2}} h\left(\frac{x}{2^k}\right).$$ This $f$ satisfies the functional equation, we just have to show that the series converges and defines a continuous function on $[-a,a]$. If we can show that the series converges uniformly on $[-a,a]$ then the our limit function $f$ will be continuous as a uniform limit of continuous functions.

For large $k$, say $k \geq k_0$, we have $|h(x/2^k)| \leq |h(0)| + \varepsilon$, by continuity of $h$, so $$\sum_{k \geq k_0} \left| \frac{x^k}{2^{k(k-1)/2}} h\left(\frac{x}{2^k}\right) \right| \leq \left(|h(0)| + \varepsilon\right) \sum_{k \geq k_0} \frac{a^k}{2^{k(k-1)/2}}$$ and the right hand side converges independently of $x$.

For the uniqueness, let $f$ and $g$ be two solutions to the functional equation. Then $f-g$ satisfies the functional equation for $h \equiv 0$. Therefore we can assume $h \equiv 0$ and show that $f \equiv 0$ is the only solution. Applying the functional equation $n$ times as above shows $$f(x) = \frac{x^n}{2^{n(n-1)/2}} f\left(\frac{x}{2^n}\right)$$ for all $n$. But $f(x/2^n)$ is bounded by continuity of $f$, so this converges to $0$ for $n \to \infty$. Thus $f \equiv 0$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.